Planning Study Of On-Grid Based Solar Power Plant At Senior High School Of Negeri 1 Meliau - Trivaldo, Angga; Husin, Fitriah; Gianto, Rudy (Journal of Electrical Engineering, Energy, and Information Technology (J3EIT), 2024)
Photovoltaic power plants (PVPs) are an environmentally friendly renewable energy source that can ensure sustainable electricity supply for schools while reducing dependence on traditional energy sources, which are not only expensive but also often harmful to the environment. Although the construction of solar power plants requires a large initial investment, technical planning such as the location of solar panels, system capacity, and integration into the existing power grid are important factors that need to be considered. This solar power plant is built on the roof of an office building that has the longest roof at 34 meters. It will be built using monocrystalline solar panels with a capacity of 670 Wp, an inverter with a capacity of 5.000 W, a solar charge controller with a capacity of 38 A, and lithium-ion batteries with a capacity of 400 Ah. This solar power plant will be planned to operate for 25 years with generated energy of 10.063 Wp.